SERUM LIPIDS ABNORMALITIES AMONG ADULT PATIENTS WITH CHRONIC PERIODONTITIS: A CASE-CONTROL STUDY - DOSKY, ALI HUSSEIN; MOUSA, HASHIM DAWOOD; SALIH, SHERWAN FERMAN; SALIH, SUZAN MOHAMMED (Journal of Duhok University, 2023)
Background and objective: Periodontitis is a chronic inflammatory condition following bacterial colonization of the gingiva. Both dyslipidemia and chronic periodontitis share common characteristics as both have multifactorial etiology and share the association with chronic systemic inflammation. The current study aimed to evaluate lipid profile levels in chronic periodontitis patients. Methods: A case-control study was conducted at a dental health polyclinic in Duhok city, Kurdistan region, Iraq. The study involved 181 individuals, 89 patients with chronic periodontitis and 92 as a control group were healthy individuals. The study duration was 4 months intervals from January 2022 to April 2022. Fast blood sample has been collected A venous blood sample has been obtained after 12 hour fasting period to measure serum lipid profile, including serum cholesterol, triglyceride, low-density lipoprotein- cholesterol (LDL-C) and high-density lipoprotein- cholesterol(HDL-C) for both groups by Cobas 6000 (Hitachi, Roch). Results: A significant difference was found in serum lipid profile of among chronic periodontitis patients as compared to healthy control (p-value < 0.0001). Moreover, a positive correlation was found between clinical attachment level score and serum cholesterol, triglyceride, and low-density lipoprotein-cholesterol, while there was a negative correlation between high-density lipoprotein-cholesterol (p-value < 0.0001). Conclusion: The mean level of serum cholesterol, triglyceride, and low-density lipoprotein-cholesterol were two times higher in patients with chronic periodontitis with lower mean levels of high-density lipoprotein-cholesterol compared to healthy control.